The Role of Artificial Intelligence (AI) in Islamic Religious Education: An Analysis of Opportunities, Risks, and Ethical Regulations - Rusdiana Rusdiana; Ani Cahyadi (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the role of Artificial Intelligence (AI) in Islamic Religious Education by examining the opportunities, risks, and ethical regulations associated with its implementation in the learning process. The research employed a qualitative-descriptive library research method through the analysis of various scientific literature, academic articles, and policy documents related to the application of AI in education and Islamic ethical perspectives. The findings indicate that AI offers significant opportunities to enhance the effectiveness of Islamic Religious Education through personalized learning materials, broader access to religious information, the development of interactive learning media, and more efficient learning assessment processes. However, the use of AI also presents several risks, including the spread of invalid religious information, the diminishing role of educators, potential algorithmic bias, and challenges to students’ moral and spiritual values. Therefore, ethical regulations based on Islamic values are needed, emphasizing the principles of responsibility, honesty, justice, and human supervision in the use of AI technology within educational environments. The novelty of this study lies in the integration of analyses on AI opportunities, implementation risks, and the formulation of ethical regulations based on Islamic perspectives comprehensively within the context of Islamic Religious Education, which has received limited attention in previous studies